Separation and Purification of Lycium barbarum Polysaccharides in Neuroinflammation by High-speed Countercurrent Chromatography - Gaofeng HAO; Yu CAO; Ning ZHAO; Jianfei LIU; Duolong DI (Shipin gongye ke-ji, 2024)
Objective: This study constructed a novel method for the separation and purification of polysaccharides from Lycium barbarum polysaccharide (LBPs) by high-speed countercurrent chromatography with aqueoust two-phase system, and investigated its effect on neuroinflammation. Methods: Through the partition coefficient (K) value and stationary phase retention rate Sf, the conditions for separating and purifying LBPs using aqueous two-phase system coupled with high-speed countercurrent chromatography (HSCCC) were screened and optimized. Preliminary structural characterisation of LBPs was performed using high performance size exclusion column-multiangle laser light scatter-refractive index detector (HPSEC-MALLS-RID), 1-phenyl-3-methyl-5-pyrazolone precolumn derivatization coupled to high performance liquid chromatography (HPLC), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analyzer (TG) and scanning electron microscopy (SEM). Moreover, the anti-neuroinflammation effect was investigated on LPS induced BV2 cell model. Results: The optimal biphasic system consisted of ethanol, ammonium sulphate, water and isopropanol had a ratio of 1.4:1.0:2.58:0.3. Under the separation conditions (900 r/min and 0.8 mL/min mobile phase flow rate), three polysaccharide fractions, named LBPs-1, LBPs-2 and LBPs-3, was isolated. Polysaccharide contents were 78.35%±1.52%, 69.03%±1.71% and 62.11%±2.31%. Molecular weights were 7.40×104 Da, 2.73×104 Da and 1.47×104 Da. The monosaccharide composition was as follows: Man:Rha:GalA:GlcA:Glu:Gal:Ara, with the molar ratios of 1.9:4.9:1.3:8.1:7.6:32.6:41.8, 2.1:4.3:1.5:8.3:5.1:28.6:37.9 and 5.9:4.6:1.1:0.7:13.8:66.8:5.3, respectively. There was also a significant difference in terms of thermal stability and micro-morphology. The LBPs exhibited varying degrees of protective activity on LPS-induced BV2 cells. Conclusions: This study would provide technical support for the efficient separation and purification of plant polysaccharides, and scientific basis for the application of LBPs in the inhibition of neuroinflammation related diseases.